2021
DOI: 10.24953/turkjped.2021.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Mild encephalopathy with reversible extensive white matter lesions in a child with acute adenoviral infection and a literature review

Abstract: Background. Mild encephalopathy with a reversible splenial lesion (MERS) is a known clinical-radiological description. However, MERS with extensive lesions (MERS type-2) is rarely associated with adenovirus. There are only three published cases of MERS type-2 associated with adenovirus infection.Case. We present a 10-year-old previously healthy girl who presented with speech difficulty and mild encephalopathy after three days of prodromal illness. The magnetic resonance imaging (MRI) revealed bilateral diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In addition, severe life-threatening complications have been reported, such as encephalopathy, encephalitis, necrotizing hemorrhagic encephalopathy, epileptic seizures, and Guillain-Barre syndrome. Although most of these severe manifestations have been reported in adult patients, few pediatric patients have such complications (Akın et al, 2021, Gaughan et al, 2021, Vraka et al, 2021. Based on a recent published meta-analysis the authors found that in patients with COVID-19-induced encephalopathy, age 70-79 years, low admission lymphocyte counts, and use of corticosteroid and anticoagulants are considered poor prognostic factors (Singh et al, 2022).…”
Section: Several Neurological Involvements Have Previously Been Repor...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, severe life-threatening complications have been reported, such as encephalopathy, encephalitis, necrotizing hemorrhagic encephalopathy, epileptic seizures, and Guillain-Barre syndrome. Although most of these severe manifestations have been reported in adult patients, few pediatric patients have such complications (Akın et al, 2021, Gaughan et al, 2021, Vraka et al, 2021. Based on a recent published meta-analysis the authors found that in patients with COVID-19-induced encephalopathy, age 70-79 years, low admission lymphocyte counts, and use of corticosteroid and anticoagulants are considered poor prognostic factors (Singh et al, 2022).…”
Section: Several Neurological Involvements Have Previously Been Repor...mentioning
confidence: 99%
“…Although the primary target of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the respiratory system, neurological manifestations, including encephalopathy, have been reported in some patients (Akın et al, 2021, Lin et al, 2020, McAbee et al, 2020, Singh et al, 2022, Vraka et al, 2021. The first case of meningoencephalitis associated with SARS-CoV-2 infection was reported in an adult patient in March 2020, with a positive specific SARS-CoV-2 ribonucleic acid (RNA) in the cerebrospinal fluid (CSF) (Poyiadji et al, 2020).…”
Section: Introductionmentioning
confidence: 99%